2017
DOI: 10.15405/epsbs.2017.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Integrated Arts Therapy Intervention In Youngsters At Risk For Delinquency

Abstract: The purpose of this study was to investigate the potential for an integrated arts therapy intervention to influence youth at risk for delinquent behavior. Toward this goal, we applied a one-group pre-post experimental design to assess the effect of an Integrated Arts Therapy Program on participants' selfreported life satisfaction, self-esteem (global and academic), mood (general and momentary), and emotional and behavioural problems (emotional, conduct, hyperactivity, peer, and prosocial behavior) in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent review of numerous studies looks at the extent to which individuals' engagement in art making is associated with prosocial traits and behaviours and can predict subjects' tendency to be prosocial seven years later and inverse (Kou et al, 2020). Other studies showed that the use of art therapy in various settings can improve prosocial behaviour such as in regular elementary students, as well as in students with emotional and behavioural problems (McDonald et al, 2019), in young offenders (Kõiv et al, 2019), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent review of numerous studies looks at the extent to which individuals' engagement in art making is associated with prosocial traits and behaviours and can predict subjects' tendency to be prosocial seven years later and inverse (Kou et al, 2020). Other studies showed that the use of art therapy in various settings can improve prosocial behaviour such as in regular elementary students, as well as in students with emotional and behavioural problems (McDonald et al, 2019), in young offenders (Kõiv et al, 2019), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This term may be translated to Czech as didaktická technika (Komosný, 2013) while it may be defined as a field of material educational means (Maňák, 2003;Rambousek, 2014), more concretely as technical instruments and devices employed for educational purposes (Palán, 2002). This definition taken from the internet andragogic dictionary provides also possible representatives of educational technology: e.g.…”
Section: Educational Technologymentioning
confidence: 99%